Comparison of Criminal Sanctions in Sharia Law and Positive Law: Jinayah Fiqh Perspective - Siti Nurjannah Lase; Layla Hasfajira Br. Tambunan; Aufiya Muhammad Syukri Alghiffary; Gilang Ade Prabowo (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study aims to examine the comparison of criminal sanctions in Sharia law and positive law, with an emphasis on the view of Jinayah Fiqh. Sharia law, based on the Qur'an and Hadith, stipulates severe punishments and often severe sanctions for certain violations, such as hudud, qisas, and ta'zir. In contrast, positive laws applied in Indonesia emphasize the principles of restorative and rehabilitative justice, with sanctions varying from prison sentences to fines. This study applies a qualitative method with a comparative analysis approach to investigate the differences and similarities in the application of sanctions in the two legal systems. The findings of the study indicate that despite fundamental differences in methods and types of punishment, the two legal systems have a similar goal, which is to achieve social justice and order. By analyzing this comparison, it is hoped that similarities will be found between the two legal systems that can enrich law enforcement practices in Indonesia. This study contributes to the academic discourse on the merging of Sharia law and positive law within the framework of legal pluralism in Indonesia.